Kesiapan Guru Pendidikan Agama Islam dalam Implementasi Kurikulum Merdeka - Dwita Nurulita; M. Yusuf Fadlulloh; A Jauhar Fuad (Mujalasat: Multidiciplinary Journal of Islamic Studies, 2023)
The Free Curriculum is a result of necessary changes in the current era, influenced by the rapid advancement of technology and the high demand for its use during the Covid-19 pandemic. This situation has prompted all education stakeholders to adapt to these developments, ultimately giving rise to the Free Curriculum as a new solution. The aim of this study is to analyze the readiness level of teachers in implementing the Free Learning curriculum issued by the Ministry of Education and Culture of the Republic of Indonesia. This research employs a qualitative method to describe the characteristics of the readiness of Islamic religious education teachers in adopting the curriculum. Data collection is conducted through a Literature Review, also known as a literature study, which is a common method for gathering secondary data. In this literature study, materials are taken from articles relevant to the research topic. The research findings indicate that teacher readiness includes steps such as: 1) Preparedness to use the prescribed books. 2) Selecting the learning experiences to be encountered by students. 3) Determining suitable learning media. 4) Readiness in the assessment process. 5) Planning the evaluation and development process. Therefore, Islamic religious education teachers consider these steps when designing learning strategies that align with the Free Curriculum. Abstrak Kurikulum Merdeka merupakan hasil perubahan yang diperlukan di era saat ini, dipengaruhi oleh kemajuan teknologi yang semakin pesat dan adanya tuntutan penggunaan teknologi yang tinggi selama pandemi Covid-19. Keadaan ini mendorong semua pihak dalam dunia pendidikan untuk menyesuaikan diri dengan perkembangan tersebut, dan akhirnya menghasilkan Kurikulum Merdeka sebagai solusi baru. Tujuan penelitian ini adalah untuk menganalisis tingkat kesiapan guru dalam mengimplementasikan kurikulum Merdeka Belajar yang dikeluarkan oleh Kementerian Pendidikan dan Kebudayaan Republik Indonesia. Penelitian ini menggunakan metode kualitatif untuk menggambarkan karakteristik kesiapan guru pendidikan agama islam dalam mengadopsi kurikulum tersebut. Pengumpulan data dilakukan melalui Studi Literatur, juga dikenal sebagai studi kepustakaan, yang merupakan metode umum untuk mengumpulkan data sekunder. Dalam studi kepustakaan ini, bahan-bahan diambil dari artikel-artikel yang relevan dengan topik penelitian. Hasil penelitian menunjukkan bahwa kesiapan guru mencakup langkah-langkah seperti: 1) Kesiapan dalam menggunakan buku yang telah ditetapkan. 2) Pemilihan pengalaman belajar yang akan dihadapi siswa. 3) Penentuan media pembelajaran yang sesuai. 4) Kesiapan dalam proses penilaian. 5) Perencanaan proses evaluasi dan pengembangan. Oleh karena itu, guru Pendidikan Agama Islam mempertimbangkan langkah-langkah ini saat merancang strategi pembelajaran yang sesuai dengan kurikulum Merdeka.